2015
DOI: 10.1186/s40064-015-1546-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of specimen type on free immunoglobulin light chains analysis on the Roche Diagnostics cobas 8000 analyzer

Abstract: The measurement of free immunoglobulin light chains is typically performed on serum; however, the use of alternative specimen types has potential benefits. Using the Freelite™ kappa and lambda free light chains assay on a Roche Diagnostics cobas 8000 c502 analyzer, we compared three specimen types (serum, EDTA-plasma and lithium heparin plasma separator gel-plasma) on 100 patients. Using Deming regression and eliminating outliers (limiting data to light chain concentrations below 400 mg/L), the three specimen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Heparinized plasma or serum samples were tested using the sFLC assay (FREELITE™, The Binding Site Ltd., Birmingham, UK) to measure κ and λ immunoglobulin FLC levels at either the Mayo Clinic or National Cancer Institute (NCI) 23 . Prior studies have shown the high intraclass correlation between FLC measures using fresh and stored serum and for the FREELITE™ kappa and lambda free light chains assay; both EDTA-plasma and lithium heparin-plasma can serve as acceptable substitutes for serum 30,31 . As previously described, the analytic sensitivity for the nephelometric FLC assay is 0.1 mg/L for a monoclonal κ or λ FLC 32 .…”
Section: Methodsmentioning
confidence: 99%
“…Heparinized plasma or serum samples were tested using the sFLC assay (FREELITE™, The Binding Site Ltd., Birmingham, UK) to measure κ and λ immunoglobulin FLC levels at either the Mayo Clinic or National Cancer Institute (NCI) 23 . Prior studies have shown the high intraclass correlation between FLC measures using fresh and stored serum and for the FREELITE™ kappa and lambda free light chains assay; both EDTA-plasma and lithium heparin-plasma can serve as acceptable substitutes for serum 30,31 . As previously described, the analytic sensitivity for the nephelometric FLC assay is 0.1 mg/L for a monoclonal κ or λ FLC 32 .…”
Section: Methodsmentioning
confidence: 99%
“…Complete blood count tests and measurements of serum IgA, IgM, IgG, IgG1, IgG2, IgG3, and IgG4 levels were conducted before and one month after vaccination. Routine immunophenotyping of peripheral blood lymphocytes, β2microglobulin, IL-6, complement components 3 and 4 (C3 and C4), lactate dehydrogenase (LDH), albumin, total protein, M protein, free light chains (FLC), IgG, IgM, IgA serum levels, plasmablast evaluation, serum pneumococcal antibody assessment, and IgG subclasses assessment were performed as described previously 9,25. Assessment of serum pneumococcal antibody was done before vaccination (on the vaccination day) and 30 days after vaccination, using a commercial ELISA test (ELIZEN Pneumococcus IgG Assay, Zentech, Belgium), which determines the concentration of anti-capsular-polysaccharide antibody specific for 23 pneumococcal serotypes (1, 2, 3, 4, 5, 6B, 7F, 8, 9N, 9V, 10A, 11A, 12F, 14, 15B, 17F, 18C, 19A, 19F, 20, 22F, 23F, 33F).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple projects focused on various aspects of assay validation, modification, or discontinuation. These included validation of plasma as an acceptable specimen for k and l free light chain analysis, 34 comparison of diazo and vanadate oxidase direct bilirubin assays, 35 validation of hematopoietic progenitor count on automated hematology analyzer for use in stem cell transplant, 51 and introduction of lamellar bodies assay for fetal lung maturity testing. A transfusion medicine-related project involved innovative use of an inexpensive device to limit blood loss for Jehovah's Witness patients.…”
Section: Other Clinical Pathology Projectsmentioning
confidence: 99%